INCIDENCE OF DIABETIC RETINOPATHY IN THE RUSSIAN FEDERATION ACCORDING TO FEDERAL STATISTICS - V. V. Neroev; O. V. Zaytseva; L. A. Mikhailova (Российский офтальмологический журнал)
Despite a comprehensive approach to the problem of diabetes mellitus (DM) and diabetic retinopathy (DR) in the Russian Federation, a number of problems persist in medical care for patients with DM. The analysis of statistical data makes it possible to assess the availability and the quality of medical care for diabetic patients in each region of the Russian Federation and to plan the distribution of resources - medicinal and technical support. This paper presents the geographical distribution analysis of DR general incidence, visibility impairment due to DR, the proportion of timely detected DR in the course of primary preventive healthcare, and the medical examination coverage. We propose that certain regional defects exist in the organization of medical care for patients with DR. For citation: Neroev V.V., Zaytseva O.V., Mikhailova L.A. Incidence of diabetic retinopathy in the Russian Federation according to Federal statistics. Russian ophthalmological journal. 2018; 11 (2): 5-9. doi: 10.21516/2072-0076-2018-11-2-5-9 (In Russian).